Analysis of the Emails From the Dutch Web-Based Intervention “Alcohol de Baas”: Assessment of Early Indications of Drop-Out in an Online Alcohol Abuse Intervention - Smink, Wouter A. C.; Sools, Anneke M.; Postel, Marloes G.; Tjong Kim Sang, Erik; Elfrink, Auke; Libbertz-Mohr, Lukas B.; Veldkamp, Bernard P.; Westerhof, Gerben J. (Frontiers in Psychiatry, 2021)
Nowadays, traditional forms of psychotherapy are increasingly complemented by online interactions between client and counsellor. In (some) web-based psychotherapeutic interventions, meetings are exclusively online through asynchronous messages. As the active ingredients of therapy are included in the exchange of several e-mails, this verbal exchange contains a wealth of information about the psychotherapeutic change process. Unfortunately, drop-out related issues are exacerbated online. We employed several machine learning models to find (early) signs of drop-out in the e-mail data from the `Alcohol de Baas' intervention by Tactus. Our analyses indicate that the e-mail texts contain information about drop-out, but as drop-out is a multidimensional construct, it remains a complex task to accurately predict who will drop-out. Nevertheless, by taking this approach, we present insight in the possibilities of working with e-mail data and present some preliminary findings (which stress the importance of a good working alliance between client and counsellor, distinguish between formal and informal language, and highlight the importance of Tactus' internet forum).